An Interpretation of the East Java MUI Fatwa on “Sound Horeg”: Bayānī, ‘Irfānī, and Burhānī Perspectives - Ach Badri Amien; M. Sa’ad Alfanny; Achmad Sholakhuddin Al Af Ghoni; Aniq, Ahmad Fathan (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2025)
Abstract: The phenomenon of “sound horeg” audio systems with bass pressure reaching 95–135 dB has caused social, health, and environmental problems in various regions of East Java. Responding to this condition, the Indonesian Ulema Council (MUI) of East Java issued Fatwa Number 1 of 2025, which stipulates that the use of “sound horeg” with excessive intensity and accompanied by practices that lead to harm is declared harām (forbidden), while reasonable use for positive activities is permitted. This study aims to explain the normative basis of the fatwa through the epistemological perspective of Muḥammad ‘Ābid al-Jābirī, covering three models of reasoning: bayānī, ‘irfānī, and burhānī. Data were collected through a literature study by examining official fatwa documents, fiqh literature, al-Jābirī’s works, and scientific articles related to the “sound horeg” phenomenon. The analysis was carried out using a qualitative-analytical approach, namely, reading the fatwa as a legal text as well as a social phenomenon to see how the three models of reasoning work. The study's findings demonstrate that the MUI combines the legitimacy of sharia texts (bayānī), ethical-spiritual considerations of society (ʿirfānī), and empirical evidence regarding the dangers of noise and social damage (burhānī). Thus, this fatwa is not merely normative but also constitutes a comprehensive epistemological response to changes in modern entertainment culture. Keywords: Fatwa, Majelis Ulama Indonesia, Sound Horeg, Bayānī–‘Irfānī–Burhānī. Abstrak: Fenomena “sound horeg” sistem audio dengan tekanan bass mencapai 95–135 dB menimbulkan persoalan sosial, kesehatan, serta gangguan lingkungan di berbagai daerah Jawa Timur. Merespons kondisi tersebut, Majelis Ulama Indonesia (MUI) Jawa Timur menerbitkan Fatwa Nomor 1 Tahun 2025 yang menetapkan bahwa penggunaan “sound horeg” dengan intensitas berlebihan dan disertai praktik yang mengarah pada kemudaratan dinyatakan haram, sedangkan penggunaan wajar untuk kegiatan positif diperbolehkan. Penelitian ini bertujuan menjelaskan dasar normatif fatwa tersebut melalui perspektif epistemologi Muḥammad ‘Ābid al-Jābirī, meliputi tiga model nalar: bayānī, ‘irfānī, dan burhānī. Data dikumpulkan melalui studi pustaka dengan menelaah dokumen resmi fatwa, literatur fikih, karya al-Jābirī, serta artikel ilmiah terkait fenomena “sound horeg”. Analisis dilakukan menggunakan pendekatan kualitatif-analitis, yaitu membaca fatwa sebagai teks hukum sekaligus fenomena sosial untuk melihat bagaimana ketiga model nalar tersebut bekerja. Hasil kajian menunjukkan bahwa MUI menggabungkan legitimasi teks syariat (bayānī), pertimbangan etika-spiritual masyarakat (ʿirfānī), serta bukti empiris mengenai bahaya kebisingan dan kerusakan sosial (burhānī). Dengan demikian, fatwa ini tidak hanya bersifat normatif, tetapi merupakan respon epistemologis yang komprehensif terhadap perubahan budaya hiburan modern. Kata Kunci: Fatwa, Majelis Ulama Indonesia, Sound Horeg, Bayānī–‘Irfānī–Burhānī.